Advances in genetic factors of adolescent idiopathic scoliosis: a bibliometric analysis - Jiang, Xiaowei; Liu, Fuyun; Zhang, Mingxuan; Hu, Weiming; Zhao, Yufeng; Xia, Bing; Xu, Ke (Frontiers in Pediatrics, 2024)
Objective This study offers a bibliometric analysis of the current situation, hotspots, and cutting-edge domains of genetic factors of adolescent idiopathic scoliosis (AIS). Methods All publications related to genetic factors of AIS from January 1, 1992, to February 28, 2023, were searched from the Web of Science. CiteSpace software was employed for bibliometric analysis, collecting information about countries, institutions, authors, journals, and keywords of each article. Results A cumulative number of 308 articles have been ascertained. Since 2006, publications relating to genetic factors of AIS have significantly increased. China leads in both productivity and influence in this area, with the Chinese Academy of Medical Sciences being the most productive institution. The most prolific scholars in this field are Y. Qiu and Z. Z. Zhu. The publications that contributed the most were from Spine and European Spine Journal. The most prominent keywords in the genetic factors of AIS were "fibrillin gene", "menarche", "calmodulin", "estrogen receptor gene", "linkage analysis", "disc degeneration", "bone mineral density", "melatonin signaling dysfunction", "collagen gene", "mesenchymal stem cell", "LBX1", "promoter polymorphism", "Bone formation", "cerebrospinal fluid flow" and "extracellular matrix". Conclusion This analysis provides the frontiers and trends of genetic factors in AIS, including relevant research, partners, institutions and countries.